Flexible agricultural index insurance products offered to horticultural producers by Banco de Seguros del Estado and the Government of Uruguay - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Following a pilot implemented in partnership with IFPRI and Banco de Seguros del Estado over the period 2013-2014, the Government of Uruguay has been implementing flexible insurance schemes for the past 6 years to cover horticultural farmers against excess rainfall in the southern horticultural regions of the country.